Evaluation of surrogate measures of pulmonary function derived from electrical impedance tomography data in children with cystic fibrosis. (26th April 2018) - Muller, Peter A; Mueller, Jennifer L; Mellenthin, Michelle; Murthy, Rashmi; Capps, Michael; Wagner, Brandie D; Alsaker, Melody; Deterding, Robin; Sagel, Scott D; Hoppe, Jordana
Abstract: Objective : Lung function monitoring by spirometry plays a critical role in the clinical care of pediatric cystic fibrosis (CF) patients, but many young children are unable to perform spirometry, and the outputs are often normal even in the presence of lung disease. Measures derived from electrical impedance tomography (EIT) images were studied for their utility as potential surrogates for spirometry in CF patients and to assess response to intravenous antibiotic treatment for acute pulmonary exacerbations (PEx) in a subset of patients. Approach : EIT data were collected on 35 subjects (21 with CF, 14 healthy controls, 8 CF patients pre- and post-treatment for an acute PEx) ages 2 to 20 years during tidal breathing and also concurrently with spirometry on subjects over age 8. EIT-derived measures of FEV1, FVC, and FEV1/FVC were computed globally and regionally from dynamic EIT images. Main results : Global EIT-derived FEV1/FVC showed good correlation with spirometry FEV1/FVC values (r  =  0.54, p  =  0.01), and were able to distinguish between the groups (p  =  0.01). Lung heterogeneity was assessed through the spatial coefficient of variation (CV) of EIT difference images between key time points, and the CVs for EIT-derived FEV1 and FVC showed significant correlation with the CV for tidal breathing (r  =  0.47, p  =  0.01 and r  =  0.50, p  =  0.01, respectively). Global EIT-derived FEV1/FVC was better able to distinguish between groups than spirometry FEV1 (F-values 776.5 and 146.3, respectively, p  <  0.01.) The same held true for the CVs for EIT-derived FEV1, FVC, and tidal breathing (F-values 215.93, 193.89, 204.57, respectively, p  <  0.01). Significance : The strong correlation between the CVs for tidal breathing, FEV1, and FVC, and the statistically significant ability of CV for tidal breathing to distinguish between healthy subjects and CF patients, and between the studied CF disease states suggests that the CV may be useful for measuring the extent and severity of structural lung disease.